PEMANFAATAN TANAH TERLANTAR DAN PROBLEMATIKA HUKUMNYA - Sinjar, M Arafah; Yuli, Yuliana; Satino; Lewoleba, Kayus Kayowuan (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract Very idealistic is when we hear the expression "A piece of land should not be left abandoned on this earth." This proposition gives us the spirit to make use of vacant land that still presents an unsightly view due to its eerie and frightening appearance. Overgrown bushes and vegetation, besides being unproductive, are also unattractive. They are far from yielding economic benefits for both the landowner and the surrounding community. They even become obstacles to the passage of shortcut users because they are overgrown and filled with frightening creatures such as snakes or beehives and other wild animals. It might even become a place for vice, crime, or other criminal activities. The scenery described above has become a common sight in this country. It is possible that such neglect has occurred due to an accumulation of land abandonment from the past that remains unresolved. It could be due to the landowner's busy schedule or perhaps because of the vastness of the land they are managing. It could also be due to the loss of resources or maybe because of the uncertainty of ownership rights related to heirs. Or they may be waiting for the land's price and value to increase before selling it again at a more enticing price. Abstrak Sangat idealis bilamana kita mendengar ungkapan “Sejengkal tanah tidak boleh terlantar di bumi pertiwi ini”. Proposisi itu memberi kita semangat untuk memanfaatkan tanah kosong yang masih menjadi pemandangan tidak elok karena menyuguhkan pemandangan yang seram dan menakutkan. Semak belukar dan tumbuh-tumbuhan, di samping tidak produktif juga tidak estetik. Jauh dari hasil yang dapat dimanfaatkan secara ekonomi oleh pemiliknya maupun warga sekitarnya. Bahkan menjadi penghalang untuk melintas pengguna jalan pintas karena tertutup dan banyak binatang yang menakutkan. Seperti ular atau sarang tawon dan binatang buas lainnya. Bahkan bisa saja lokasi tersebut hanya dijadikan tempat maksiat dan kejahatan atau kriminal lainnya. Pemandangan tersebut di atas sudah menjadi pemandangan umum di negeri ini. Bisa saja hal tersebut terlantar karena merupakan akumulasi penelantaran tanah yang terjadi pada masa lalu yang tidak terselesaikan. Kesibukan atau mungkin saja karena luasnya tanah yang ditangani pemiliknya. Atau karena kehilangan sumber daya penggerak. Atau mungkin karena ketidakpastian hak milik yang berkaitan dengan ahli waris. Atau menunggu harga dan nilai tanah tersebut meninggi. Untuk dijual kembali dengan harga yang cukup menggairahkan.